PENGARUH PROFESIONALISME BIDAN TERHADAP KUALITAS PELAYANAN KESEHATAN IBU DAN ANAK DI PUSKESMAS TATELU - TUEGEH, LIVEN JOLANDA; RUMAPEA, PATAR; KOLONDAM, HELLY (Sam Ratulangi University, 2017)
Abstract: this research aims to determine the influence of midwives profesionalisme on the quality of maternal and childhealth services at tatelu Community Health Center in Dimembe Sub-District North Minahasa Regency. This research usesquantitative method. The respondents in this research amounted to 36 patients were health visitors of maternal and child attatelu community health centre. Instrument and data collection techniques used are questionnaires and assited by interviewsand observation. The data analysis techniques used for hypothesis testing is the correlation coefficient analysis and simplelinear regression analysis assited by SPSS 21.0 data processing program. Based on the result of this study, midwivesprofessionalism has a significant effect on the quality of maternal and child health services at tatelu community healthcentre. The result of the analysis in this study showed that there is a positive relationship between midwives professionalismvariables and maternal and child health service quality variables with r-count = 0,766 greater than t-table with df (N-2 =36-2 = 34) at level 0,01 = 0.2785. If inserted into a simple regresstion equation then the value is Y = 1,336 + 0,971 X + e,with correlation coefficient (R) = 0,766. This number indicates that the relationship between the independent variable (X)and the dependent variable (Y) in the â€œstrongâ€ category as proposed by sugiyono is at the interval of 0,60-0,799. Thecorrelation and determination of midwives professionalism variable on the quality of maternal and child health services isreal and significant at 0,01 or 99% confidence level, as shown in the significant test (t-test) where the t-count = 6,958 is fargreater that t-tabel value at significance level of 0,01. As for the hypothesis put forward by the author is the alternative (Ha)states that â€œthe higher (good) level of midwives professionalism, the higher the quality of maternal and child health servicesâ€has been tested and real, can be accepted convincingly. Then the determination coefficient value (R2) = 0,587 indicates thatthe variable (X) of midwives professionalism contributes 58, 7% to the development of variable (Y) quality of maternal andchild health services at tatelu community health centre in dimembe sub-district north minahasa regency, while theremaining 41, 3% is influenced by other factors that are outside of this research.Keyword: professionalism, midwives, quality, health services